Estimation of GPS Receiver Parameters with Re-reference System and Signal Simulator - Kluga, A.; Kluga, J.; Semjonova, V.; Grabs, E. (Elektronika ir Elektrotechnika, 2008)
Results of satellite system users’ devices testing using the Re-reference system and signal simulator CTR4500 are presented. Testing was made in the laboratory with metallized windows and in reflectionless camera SAC3. Testing results have shown the possibility to use Re-reference system with receiver in static mode for precision estimation, and to define dynamic errors in laboratory with metallized windows using the satellites system signal simulator. Ill. 10, bibl. 3 (in English, summaries in English, Russian and Lithuanian).